The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0014-5793(02)03235-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus type 1 replication by P‐stereodefined oligo(nucleoside phosphorothioate)s in a long‐term infection model

Abstract: Oligo(nucleoside phosphorothioate)s (S-ODNs), if prepared by conventional methods, consist of a mixture of diastereomers by virtue of the asymmetry of the phosphorus atom involved in the internucleotide linkages. This may affect the stability of the complexes formed between S-ODNs and complementary oligoribonucleotides, which is commonly accepted as the most important factor in determining the efficacy of an antisense approach. Using HIV-1-infected MOLT-4 cells via a long-term culture approach, we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…PS-ODNs of mixed diastereomeric linkages show intermediate abilities [ 163 , 164 ]. It has been indicated that nuclease stability is one of the most important factors for PS-ODN efficacy [ 165 ], and hence the stereocontrolled synthesis of antisense PS-ODNs has been well investigated (for a review see [ 163 ]).…”
Section: Antisense Oligonucleotides Analogues and Mimicsmentioning
confidence: 99%
“…PS-ODNs of mixed diastereomeric linkages show intermediate abilities [ 163 , 164 ]. It has been indicated that nuclease stability is one of the most important factors for PS-ODN efficacy [ 165 ], and hence the stereocontrolled synthesis of antisense PS-ODNs has been well investigated (for a review see [ 163 ]).…”
Section: Antisense Oligonucleotides Analogues and Mimicsmentioning
confidence: 99%
“…One such example is the phosphorothioate oligodeoxyribonucleotides (PS‐ODNs) obtained by replacing one of the nonbridging oxygens of the phosphodiester bonds of DNA with sulphur (Rasmussen et al , 2007). Nuclease stability is one of the most important characteristics of PS‐ODNs (Inagawa et al , 2002). Their mechanism of action involves the binding to target mRNA and the activation of RNase H, resulting in mRNA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the sense of P-chirality of PS-oligos upon their antiviral activity was tested by Takaku and co-workers, who showed that the 28 mer [All-S P -PS]-d(CGCTCTCGCTCCCATCTC TCTCCTTCTA) directed to the gag mRNA completely suppressed the expression of the HIV-1 gag p24 antigen in long-term HIV-1 infected cells for 30 days [199]. In contrast, the cells treated with [All-R P ]-oligomer showed a high level of HIV-1 replication at 16 days.…”
Section: Cccgggagaaga C a A A Aaaactctacgc 5'mentioning
confidence: 99%